Fuzzy analytic hierarchy process and targeting for inter-plant chilled and cooling water network synthesis - Leong, Yik Teeng; Tan, Raymond R.; Aviso, Kathleen B.; Chew, Irene Mei Leng (Journal of cleaner production, 2016)
In recent years, the concept of industrial symbiosis (IS) has led to improvements in resource efficiency that may not be possible with individual industrial plants acting independently. One specific aspect is to achieve economies of scale by having multiple companies located in close proximity in order to share common utilities, such as chilled and cooling water. Together, these industrial plants may form an inter-plant chilled and cooling water network (IPCCWN) to achieve greater overall cost savings. Some issues faced by an IPCCWN include network reliability problems due to the consistency of sources' availability, and cost savings allocations for IPCCWN synthesis due to the subjectivity of human preference on decision making. Thus, there exists a need for a decision-making tool to determine a feasible solution that will satisfy all industrial plants in the IPCCWN. In this work, a multi-objective linear programming model is developed to synthesize IPCCWN that achieves maximum cost savings. Next, a Pareto optimal solution is selected using fuzzy analytic hierarchy process (FAHP) approach. This solution gives the best balance of performance for a set of pre-defined qualitative and quantitative criteria, which is able to account for subjectivity that cannot be addressed from a purely mathematical programming standpoint.